Exploring the biological behavior of Heat shock protein (HSPs) for understanding the Anti-ischemic stroke in humans. Issue 4 (April 2022) - Manikandan, Palanisamy; Vijayakumar, Rajendran; Alshehri, Bader; Senthilkumar, Subramanian; Al-Aboody, Mohammad Saleh; Veluchamy, Alaguraj; Haribaskar, R.
Abstract: Background: An ischemic stroke can be caused by thrombosis and ischemia, which is a major public health problem around the world, resulting in severe disability and a high death rate. The goal of this work is to examine and target various heat shock proteins (HSPs) via their interacting partners, which may have an anti-ischemic stroke impact. Methods: Various heat shock proteins are identified and used for construction of PPI network through STRING webserver. Networks are analysed and visualized using the cytoscape for checking the protein-protein interactions. Along with this, multiple cytoscape based modules are integrated for the analysis of results, and Gene Ontology results are analysed using GOView. Results: The core PPI network was revealed with 129 nodes and 1174 edges. Through Gene ontology (GO) and KEGG enrichment analysis the promising function of HSPs in two important signaling pathways were mainly recorded, representing the HSPs are necessary for repair and activations of brain cells during ischemic stroke. In addition, the study is revelation for targeting multiple HSPs via their interacting partners, which can provide anti-ischemic stroke effect. Conclusion: Overall, this finding provides a network-based framework for future research on HSP as therapeutic molecules for anti-ischemic stroke related applications.